Über die Existenz von invarianten Finslerschen Metriken in homogenen Räumen - Jonušauskas, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Ионушаускас. О существовании инвариантных финслеровых метрик в однородных пространствахA. Jonušauskas. Apie invariantinių Finslerio metrikų egzistenciją homogeninėse erdvėse